1989
DOI: 10.1111/j.1398-9995.1989.tb02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of inhaled budesonide delivered either via pressurized metered dose inhaler or Turbuhaler®

Abstract: The aim of this open, randomized cross-over study was to compare the efficacy and safety of inhaled budesonide administered either via a pressurized metered dose inhaler with a 750 ml spacer attached, or via a new dry powder inhaler, Turbuhaler, in 28 patients with stable bronchial asthma. During the 2-week run-in period, the patients received their ordinary inhaled steroid treatment. This was followed by two 4-week periods of active treatment with inhaled budesonide given via Turbuhaler or pressurized MDI. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 7 publications
3
52
1
Order By: Relevance
“…Earlier we performed two other pharmacokinetic studies with budesonide given via Nebuhaler to children [11,12] [14][15][16][17]. On the other hand Turbuhaler would also be expected to have a higher systemic activity than Nebuhaler.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier we performed two other pharmacokinetic studies with budesonide given via Nebuhaler to children [11,12] [14][15][16][17]. On the other hand Turbuhaler would also be expected to have a higher systemic activity than Nebuhaler.…”
Section: Discussionmentioning
confidence: 99%
“…No corresponding reduction could be obtained in patients continuing on BDP via pMDI, again suggesting greater clinical efficacy of the TH device [13]. ENGEL et al [17] described a significant increase in morning peak flow in patients with chronic stable asthma treated with budesonide via TH, compared to pMDI, although there was no difference in FEV1.…”
Section: Discussionmentioning
confidence: 98%
“…This means that paradoxical bronchoconstriction to β 2 -agonists is not inevitably a classeffect, but can be related to exposure to a specific β 2 -agonist and not to others [9]. In a detailed appraisal of the problem, ENGEL et al [10] concluded that a rapid cooling of the upper airways produced with CFCs, plus the irritant effect of the nondrug components, were producing the paradoxical constrictor response. Although the mean maximum fall in sGaw was similar following inhalation of terbutaline and placebo via p-MDI after placebo, the effect lasted longer and was not followed by bronchodilation.…”
Section: Discussionmentioning
confidence: 99%